Level of Volleyball Knowledge and Underwear Passing Ability - Sahabuddin Sahabuddin; Hikmad Hakim; Awaluddin Awaluddin; M. Imran Hasanuddin (Journal Coaching Education Sports, 2024)
This research is a descriptive research type that uses a "Survey" research design. This research aims to determine; (1) how the volleyball game knowledge of class V students of UPT SD Negeri Mangkura 1 Makassar City; and (2) how is the underhand passing ability of class V students of UPT SD Negeri Mangkura 1 Makassar City. The population is all class V students of UPT SD Negeri Mangkura 1 Makassar City. The sample used was 25 class V students. The sampling technique was simple random sampling. The data analysis technique used was descriptive analysis. The results of the study showed that; (1) The volleyball game knowledge of class V students of UPT SD Negeri Mangkura 1 Makassar City is in the high category, with a percentage of 36.00 percent; (2) The underhand passing ability of class V students of UPT SD Negeri Mangkura 1 Makassar City is in the medium category, with a percentage of 52.00 percent.